A Survey on Key(s) and Keyless Image Encryption Techniques - Ranjan Kumar H. S.; Fathimath Safeeriya S. P.; Aithal Ganesh; Shetty Surendra (Cybernetics and Information Technologies, 2017)
As in recent years digital data transmission and image application have been increasing, maintaining secure transmission of image is of high importance. Image Encryption is implemented to achieve security on image applications. This paper exhibits a survey on various existing image encryption techniques. The paper mainly focuses on two types: Image encryption with Key(s) and Image Encryption without Key(s). In addition it also describes several properties of a good image encryption technique. The paper presents a survey of most popular algorithms and research papers that are related with different image encryption techniques.